Applied Chemistry - Roussak, O.V.; Gesser, H.D. (Springer, 2013)
The first edition of this book appeared 10 years ago. This book is the result of teaching in the Applied Chemistry (Dr. H.D. Gesser, the Chemistry 2240 course) as well as in the Water Quality Analysis for Civil Engineers (Dr. O.V. Roussak, the CHEM 2560 course) to second year engineering students for many years at the University of Manitoba (Winnipeg, Manitoba, Canada). Much has transpired in science during this period and that includes applied chemistry. The major change in this new edition that becomes obvious is the addition of several (eight) experiments to accompany the book and the course for which it was intended. A new solutions manual is also a valuable asset to the second edition of the book. Chemistry is primarily an experimental science and the performance of a few experiments to accompany the text was long considered while the course was taught. The choice of experiments we include was determined by the equipment that is usually available (with one or two possible exceptions) and by the expected usefulness of these experiments to the student, who will eventually become a practicing professional, and to the cost that is involved in student time. We welcome any reasonable and inexpensive additional experiments to introduce for the next edition of our book and topics to include in the next edition.
A Textbook for Engineers and Technologists